Dipeptidyl peptidase‐4 inhibition improves cardiac function in experimental myocardial infarction: Role of stromal cell‐derived factor‐1α. (4th March 2015) - Connelly, Kim A.; Advani, Andrew; Zhang, Yanling; Advani, Suzanne L.; Kabir, Golam; Abadeh, Armin; Desjardins, Jean‐Francois; Mitchell, Melissa; Thai, Kerri; Gilbert, Richard E.
Abstract: Background: In addition to degrading glucagon‐like peptide‐1 (GLP‐1), dipeptidyl peptidase‐4 (DPP‐4) inactivates several chemokines, including stromal cell‐derived factor‐1 α (SDF‐1 α ), a pro‐angiogenic and cardiomyocyte protective protein. We hypothesized that DPP‐4 inhibition may confer benefit following myocardial infarction (MI) in the diabetic setting as a consequence of enhanced SDF‐1 α availability rather than potentiating GLP‐1. To test this we compared the effects of saxagliptin with those of liraglutide and used the SDF‐1 α receptor (CXCR4) antagonist plerixafor. Methods: Studies were conducted in streptozotocin‐diabetic rats. Rats were randomized to receive saxagliptin (10 mg/kg per day), liraglutide (0.2 mg/kg, s.c., b.i.d.), plerixafor (1 mg/kg per day, s.c.), saxagliptin plus plerixafor or vehicle (1% phosphate‐buffered saline). Two weeks later, rats underwent experimental MI, with cardiac function examined 4 weeks after MI. Results: Glycemic control and MI size were similar in all groups. Four weeks after MI, mortality was reduced in saxagliptin‐treated rats compared with vehicle treatment ( P  < 0.05). Furthermore, rats receiving saxagliptin had improved cardiac function compared with vehicle‐treated rats ( P  < 0.05). Antagonism of CXCR4 prevented the improvement in cardiac function in saxagliptin‐treated rats and was associated with increased mortality ( P  < 0.05). Conclusion: Saxagliptin‐mediated DPP‐4 inhibition, but not liraglutide‐mediated GLP‐1R agonism, improved cardiac function after MI independent of glucose lowering. These findings suggest that non‐GLP‐1 actions of DPP‐4 inhibition, such as SDF‐1 α potentiation, mediate biological effects.